Analilis Kebutuhan Lahan Parkir Mobil di Rsud Dr. Zainoel Abidin Kota Banda Aceh - Asriandi, Asriandi; Meliyana, Meliyana; Silviana, Mery; Amin, Amri (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research aims to determine the characteristics of four-wheeled vehicle parking at RSUD Dr. Zainoel Abidin, This research method uses a calculation survey method at the boundaries of the planning area (cordon count), namely survey officers carry out supervision at monitoring posts. This is to obtain data on parking provision (supply) and parking demand (demand) in the car parking area Dr. Hospital Zainoel Abidin Banda Aceh City. The results of this research were that parking volume was obtained during a 1 day time interval. The highest parking volume occurred on Monday, 994 cars/day. The highest parking accumulation at 1 hour intervals for 3 days occurred on Monday at 13.00-14.00 at 285 cars/hour. Parking capacity for the 3 days of research based on the analysis results was 92 vehicles/hour with a parking duration of 1.75 hours/vehicle. The highest parking index at 1 hour intervals for 3 days occurred on Monday at 13.00-14.00 at 3.1. The parking turnover rate for 10 hours/day for 3 days of observation occurred on Monday at 0.61 hours/vehicle/SRP. Analysis of the highest unaccommodated parking demand occurred on Monday at 208 plots, while currently the available parking plots are 161 SRP, so it is necessary to increase the number of plots by 47 SRP.